2014
DOI: 10.1080/14779757.2014.910131
|View full text |Cite
|
Sign up to set email alerts
|

“That chair work thing was great”: a pilot study of group-based emotion-focused therapy for anxiety and depression

Abstract: Emotion-focused therapy (EFT) is an evidence-based treatment for depression and it has shown promise for the treatment of anxiety. Only one other published study has examined EFT in a group therapy setting. Using mixed-methods, the current study explored the feasibility and outcomes of an EFT group with adults referred for anxiety and depression. Pre-, post-, and 12-month follow-up measures of depression, anxiety, and difficulties in emotion regulation were administered in addition to a semi-structured intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 34 publications
(45 reference statements)
3
9
0
Order By: Relevance
“…The reductions in binge episode frequency are consistent with the results from research on other group treatments for eating disorders (Jacobi, Dahme, & Dittman, 2002;Riess, 2002;Shiina, Nakazato, Mitsumori, & Koizumi, 2005). Our findings are consistent with those of Lafrance Robinson et al (2014) in showing that a group EFT approach may result in successful client outcomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reductions in binge episode frequency are consistent with the results from research on other group treatments for eating disorders (Jacobi, Dahme, & Dittman, 2002;Riess, 2002;Shiina, Nakazato, Mitsumori, & Koizumi, 2005). Our findings are consistent with those of Lafrance Robinson et al (2014) in showing that a group EFT approach may result in successful client outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…The theoretical foundations of EFT are well-developed (Greenberg & Watson, 2005) and outcome research has found EFT to be helpful in treating problems including depression (Greenberg & Watson 1998). In research EFT is typically delivered in 16 individual weekly sessions and a recently published study found that a group approach for individuals with anxiety and depression was effective (Lafrance Robinson, McCague, & Whissell, 2014).…”
mentioning
confidence: 99%
“…They indicated that their design was "the most suitable and comprehensive approach to ascertain the effectiveness of the interventions whilst also gathering participants' views on the intervention" (Lopez et al, 2014, p. 412). Similar findings emerged in other studies where qualitative data were indicated to have deepened the findings by going beyond statistical testing (e.g., Finucane & Mercer, 2006;Grocke et al, 2014;Herrera-Mercadal et al, 2015;Lucock et al, 2015;Lucre & Corten, 2013;Robinson, McCague, & Whissell, 2014;Werbart et al, 2015). This reinforces the value derived from speaking with participants to better conceive the fruitfulness of interventions.…”
Section: Integration Of Clients' Perceptions Via Mixingsupporting
confidence: 86%
“…Perhaps associated with the ability to embrace clients' perceptions of treatment, the use of mixed methods in group psychotherapy research became clear (frequency = 32.26%; n = 10). Several studies used mixed methods designs to study, often among small samples for pilot or exploratory purposes, group interventions (Bensimon, Amir, & Wolf, 2012;Carr et al, 2011;Down et al, 2011;Grocke et al, 2014;Heriot-Maitland, Vidal, Ball, & Irons, 2014;Lucre & Corten, 2013;Robinson et al, 2014;Swank & Shin, 2015;Tasca et al, 2011). Using mixed methods for smaller sample, exploratory group research allowed these researchers to assess "outcome efficacy and [use] qualitative methods in investigating therapeutic processes" (Down et al, 2011, p. 49).…”
Section: Understanding Group Psychotherapymentioning
confidence: 99%
“…EFT has been successful in enhancing emotional processing and regulation in other disorders, including depression (e.g., Goldman, Greenberg, & Angus, 2006;Greenberg & Watson, 2005;Robinson, McCague, & Whissell, 2014) and complex trauma (e.g., Holowaty & Paivio, 2012;Paivio & Nieuwenhuis, 2001;Paivio & Pascual-Leone, 2010). Recently, evidence has also been mounting for the efficacy of EFT in the treatment of anxiety disorders (Shahar, Bar-Kalifa, & Alon, 2017;Timulak et al, 2017;Watson & Greenberg, 2017).…”
Section: Emotional Factors and Eftmentioning
confidence: 99%